The training of experimental skills in the high school physics teacher in São Luís do Maranhão - Nascimento, Ubiraci Silva; Oliveira, Fernando Lima de; Neto, André Santos da Silva; Filho, José de Ribamar Pestana; Beckman, Valter Valder Reis (Seven Editora, 2023)
This work is the result of the results of a master's thesis in education, referring to the reality of the teaching of Experimental Physics in the middle cycle in São Luís – MA, where the problem found was the lack of experimental skills of teachers who use the laboratories of their schools and also, how to promote experimental classes in schools that do not have laboratories. A Theoretical Practical Model that develops experimental skills in the high school teacher in the area of Physics is proposed. The model makes use of the theory of human activity in the improvement of the teaching-learning process. In the applied methodology, different research methods were used: theoretical methods (analysis-synthesis, induction and deduction; modeling and systemic-structural) and empirical methods (unstructured interview, participatory observation and questionnaires). 04 four high schools in São Luís were diagnosed, being 02 public and 02 private. The results of the diagnosis showed that even in schools that have laboratories, 85% of teachers do not have any ability to develop experimental classes of a practical nature. After the application of the proposed methodology in the schools, a partial validation of the results was promoted, applying the PNI technique (Positive, Negative and Interesting Points), where 90% of the teachers began to apply the model in their work practice.  DOI:https://doi.org/10.56238/ptoketheeducati-032